Antimicrobial Resistance: A Silent Pandemic Threat - Shrimali, Gaurishanker Pashabhai (International Journal of Medical Research, 2025)
Antimicrobial resistance (AMR) poses a formidable threat to global health, often termed a "silent pandemic" due to its insidious spread and devastating impact. This perspective examines the origins, scope, implications, and potential solutions to AMR, emphasizing its urgency. Driven by overuse of antimicrobials in medicine and agriculture, inadequate infection control, and limited diagnostics, AMR caused 1.27 million deaths in 2019, with projections of 10 million annual deaths by 2050. Gram-negative bacteria, such as Escherichia coli and Klebsiella pneumoniae, increasingly resist last-resort drugs, complicating treatments and routine procedures. Economically, AMR could cost US1 trillion in healthcare and trillions in GDP losses by 2050. Low- and middle-income countries face disproportionate burdens, exacerbating global inequities. Solutions include antimicrobial stewardship, incentivizing new drug development via models like the PASTEUR Act, and enhancing global surveillance through WHO’s GLASS. This article underscores AMR’s One Health nature, linking human, animal, and environmental health, and calls for urgent, coordinated action to integrate AMR into broader health agendas. Biomedical communities must lead in policy advocacy and innovation to avert a crisis that threatens decades of medical progress.